1973
DOI: 10.1083/jcb.56.1.191
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Cell Fractionation Procedure for the Preparation of Rat Liver Membrane-Bound Ribosomes

Abstract: A cell fractionation procedure is described which allows the preparation from rat liver of a rough microsome population containing almost 50% of the membrane-bound ribosomes of the tissue. The fraction is not contaminated with free ribosomes or smooth microsomes, and, by various other criteria, is suitable for studies of ribosome-membrane interaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0

Year Published

1978
1978
2005
2005

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(67 citation statements)
references
References 29 publications
3
64
0
Order By: Relevance
“…Gradients were unloaded in 1-ml fractions, and fractions containing ribosomal subunits were pooled as judged by the A 260 profile of each gradient (22). To remove salt and concentrate the ribosomal subunits, samples were diluted with 1 volume of RBB and sedimented (100,000 rpm, 1 h, 4°C, TLA-100.4 rotor, Beckman).…”
Section: Methodsmentioning
confidence: 99%
“…Gradients were unloaded in 1-ml fractions, and fractions containing ribosomal subunits were pooled as judged by the A 260 profile of each gradient (22). To remove salt and concentrate the ribosomal subunits, samples were diluted with 1 volume of RBB and sedimented (100,000 rpm, 1 h, 4°C, TLA-100.4 rotor, Beckman).…”
Section: Methodsmentioning
confidence: 99%
“…(b) It was also demonstrated that, while ribosomes not containing nascent chains can be bound to specific receptors on the ER membranes, such ribosomes are removed from the membranes when microsomes are incubated in media of high salt concentration (2,3,22). On the other hand, ribosomes containing long nascent polypeptides can only be detached from microsomal membranes by treatment with puromycin, which releases the nascent polypeptide chain from the ribosome (2,3), or by destructive methods that unfold the ribosomal subunits (189).…”
Section: Role Of Cotranslational Insertion Signals In Determining Thementioning
confidence: 99%
“…On the other hand, ribosomes containing long nascent polypeptides can only be detached from microsomal membranes by treatment with puromycin, which releases the nascent polypeptide chain from the ribosome (2,3), or by destructive methods that unfold the ribosomal subunits (189). Furthermore, it was shown that as the aminoterminal portion of the nascent chain emerges from the ribosome it enters into a relationship with the membrane that protects the extraribosomal segment of the nascent chain from attack by added proteases, unless detergents are added to dissolve the membranes (185).…”
Section: Role Of Cotranslational Insertion Signals In Determining Thementioning
confidence: 99%
“…The carbon-oxygen bond lengths in the carboxyl group are approximately equal, corresponding to a carboxylate form. The nature of lactim-lactam tautomerism in bilirubin is contro versial [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] . In this study the values of carbon nitrogen and carbon-oxygen bond lengths in the terminal rings, the experi mental evidence in these rings of a hydrogen bound to the nitrogen atom, and the large value observed for the C4 C5-C6 bond angle-as a consequence of H • • H repulsion in the oxodipyrromethene portion (see Fig.…”
mentioning
confidence: 99%